Water requirements and fruit development rate of Cantaloupe melons cultivated in summer-autumn - Andrian, Andre; Rezende, Roberto; Soares Wenneck, Gustavo; Villa e Vila, Vinícius; de Souza Terassi, Daniele; Maldonado da Silva, Lucas Henrique (Comunicata Scientiae, 2022)
The knowledge regarding the crop water demand and its vegetative development is the basis for any agronomic scientific research. This study determined evapotranspiration, crop coefficient, fruit growth rate, stem, and photosynthetic activities of the melon. The experiment was conducted in a protected environment at the Technical Irrigation Center (CTI) of the Universidade Estadual de Maringá (UEM) in Maringá-Pr. The hybrid used was the melon Cantaloupe Torreon grown vertically. Irrigation was carried out via drip based on accumulated evapotranspiration. Reference evapotranspiration was estimated by the Penman-Monteith-FAO method using data from an automatic weather station, and crop evapotranspiration was measured using constant groundwater lysimeters. Caliper performed measurements of the plant’s lap and fruit in formation. The SPAD index measurements occurred on the third leaf of the main stem and the leaf closest to the fruit. The melon’s water demand was 388.16 mm. The crop coefficient values obtained were: 0.95, 1.03, and 0.99 for the initial, intermediate, and final stages. The growth rate of the cervix increased from 7 mm to 35th day after transplantation. In 14 days, the equatorial growth of the fruit was 98 mm. The SPAD index registered a maximum of 105 for the third leaf and 112 for the fruit leaf.